2018
DOI: 10.3389/fnsyn.2018.00023
|View full text |Cite
|
Sign up to set email alerts
|

The First 100 nm Inside the Pre-synaptic Terminal Where Calcium Diffusion Triggers Vesicular Release

Abstract: Calcium diffusion in the thin 100 nm layer located between the plasma membrane and docked vesicles in the pre-synaptic terminal of neuronal cells mediates vesicular fusion and synaptic transmission. Accounting for the narrow-cusp geometry located underneath the vesicle is a key ingredient that defines the probability and the time scale of calcium diffusion to bind calcium sensors for the initiation of vesicular release. We review here the time scale, the calcium binding dynamics and the consequences for asynch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 58 publications
1
23
0
3
Order By: Relevance
“…The results demonstrated the existence of constitutive differences in the PF terminals of lobules V and X of CB 1 ‐WT mice. These distinct features might reflect different synaptic vesicle trafficking dynamics and release probabilities that could have functional consequences on synaptic plasticity (Guerrier & Holcman, ; Singer & Diamond, ). In primary granule cell cultures, PF terminals have relatively large releasable vesicle pool, rapid vesicle replenishment, loose coupling of Ca 2+ channels and releasable vesicles as well as strong dependence of facilitation on fast intracellular Ca 2+ buffering (Kawaguchi & Sakaba, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results demonstrated the existence of constitutive differences in the PF terminals of lobules V and X of CB 1 ‐WT mice. These distinct features might reflect different synaptic vesicle trafficking dynamics and release probabilities that could have functional consequences on synaptic plasticity (Guerrier & Holcman, ; Singer & Diamond, ). In primary granule cell cultures, PF terminals have relatively large releasable vesicle pool, rapid vesicle replenishment, loose coupling of Ca 2+ channels and releasable vesicles as well as strong dependence of facilitation on fast intracellular Ca 2+ buffering (Kawaguchi & Sakaba, ).…”
Section: Discussionmentioning
confidence: 99%
“…Differences observed in CB 1 ‐KO relative to CB 1 ‐WT could be particularly relevant as the synaptic vesicle distribution in CB 1 ‐KO could affect the exposure of synaptic vesicles to the calcium sources that dictate vesicle dynamics (Böhme, Grasskamp, & Walter, ; Guerrier & Holcman, ) that are crucial for synaptic plasticity (Atwood, Lovinger, & Mathur, ; Böhme et al, ; Chen, Das, Nakamura, DiGregorio, & Young, ; Eggermann, Bucurenciu, Goswami, & Jonas, ; Guerrier & Holcman, ; Holderith et al, ; Indriati et al, ; Keller et al, ; Sheng et al, ). The structural basis of synaptic plasticity is mediated by the dynamics of the presynaptic architecture (Bruckner, Zhan, & O'Connor‐Giles, ).…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of FPT studies have focused on the time it takes a given single searcher to find a target. However, several recent works and commentaries have shown that the relevant timescale in many systems is actually the time it takes the fastest searcher(s) to find a target out of a large group of searchers [11,12,13,14,15,16,17,18,19,20]. For example, roughly N = 10 8 sperm cells search for an egg in human reproduction, but fertilization occurs as soon as a single sperm cell finds the egg [21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Several exciting investigations and commentaries have recently announced a paradigm shift in studying cellular activation rates [1,2,3,4,5,6,7,8,9,10,11,12,13]. This important work has produced new questions, calls for more investigation, and intriguing conjectures to explain the seeming "redundancy" that marks many biological systems [2].…”
Section: Introductionmentioning
confidence: 99%